The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1582-4934.2009.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and catalytic heterogeneity of polyclonal myelin basic protein‐hydrolyzing IgGs from sera of patients with multiple sclerosis

Abstract: Human myelin basic protein (hMBP)-hydrolyzing activity was recently shown to be an intrinsic property of antibodies (Abs) from multiple sclerosis (MS) patients. Here, we present the first evidence demonstrating a significant diversity of different fractions of polyclonal IgGs (pIgGs) from MS patients in their affinity for hMBP and in the ability of pIgGs to hydrolyze hBMP at different optimal pHs (3–10.5). IgGs containing λ- and κ-types of light chains demonstrated comparable relative activities in the hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(129 citation statements)
references
References 39 publications
7
122
0
Order By: Relevance
“…It was recently shown that incubation of many individual IgGs with iodoacetamide (a specific inhibitor of thiol proteases) or pepstatin A (a specific inhibitor of acidic proteases) has moderate effect (5-15%) on SLE Ab-dependent hydrolysis of MBP [9]; the same was demonstrated for MS IgGs, IgAs and IgMs [27][28][29][30][31]. However, PMSF, AEBSF (specific inhibitors of serine proteases), and EDTA (an inhibitor of metalloproteases) significantly suppressed the proteolytic activity of SLE and MS pIgGs in the case of MBP and OPs as substrates [9].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…It was recently shown that incubation of many individual IgGs with iodoacetamide (a specific inhibitor of thiol proteases) or pepstatin A (a specific inhibitor of acidic proteases) has moderate effect (5-15%) on SLE Ab-dependent hydrolysis of MBP [9]; the same was demonstrated for MS IgGs, IgAs and IgMs [27][28][29][30][31]. However, PMSF, AEBSF (specific inhibitors of serine proteases), and EDTA (an inhibitor of metalloproteases) significantly suppressed the proteolytic activity of SLE and MS pIgGs in the case of MBP and OPs as substrates [9].…”
Section: Discussionmentioning
confidence: 89%
“…No activity was found for IgG fraction of healthy donors in the hydrolysis of MBP or different OPs (Fig. 1) [27][28][29][30][31]. The sites of MBP cleavage by MS IgGs determined by mass spectrometry were localized within four known immunodominant regions of MBP [31].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations